Implementing a Novel Workplace Smoking Cessation Intervention Targeting Hispanic/Latino Construction Workers: A Pilot Cluster Randomized Trial. (December 2021) - Asfar, Taghrid; Arheart, Kristopher L.; McClure, Laura A.; Ruano-Herreria, Estefania C.; Dietz, Noella A.; Ward, Kenneth D.; Caban-Martinez, Alberto J.; Samano Martin Del Campo, Daniel; Lee, David J.
Background: U.S. Hispanic/Latino construction workers constitute a large and historically underserved group in terms of smoking cessation services. Using formative research, we developed a worksite smoking cessation intervention tailored to the life/work circumstances of these workers. Aims: This study aims to examine the feasibility, acceptability, and potential efficacy of the developed intervention "Enhanced Care" (EC; one group behavioral counseling session provided around the food truck + fax referral to tobacco quitline [QL] + 8-week nicotine replacement treatment [NRT]) compared with "Standard Care" (SC; fax referral to tobacco QL + 8-week NRT) in a pilot, two-arm, cluster randomized controlled trial. Method: In collaboration with construction site safety managers, a sample of 17 construction sites (EC: nine sites/65 smokers; SC: eight sites/69 smokers) was enrolled. Participants received two follow-ups at 3 and 6 months after enrollment. Feasibility outcomes were enrollment rate, adherence to treatment, and 6-month retention rates. The primary efficacy outcome was 6 months prolonged abstinence verified by expired carbon monoxide <10 ppm. Results: Enrollment rate was high (85.9%). Six-month follow-up rates were acceptable (EC = 76.9%, SC = 66.6%). Adherence to treatment was better in the EC group (received worksite intervention: EC = 93.8%, SC = 88.4%; contacted by QL: EC = 49.2%, SC = 40.6%). Abstinence rates were 27.7% for the EC and 20.3% for the SC ( p = .315). Discussion: The developed intervention was feasible and acceptable, and it substantially improved abstinence among Hispanic/Latino workers. The involvement of safety managers was essential to the implementation of the intervention. Training safety managers to deliver the intervention has great potential to implement a sustainable smoking cessation service in the construction sector.